Isolation, optimization and molecular characterization of lipase producing bacteria from contaminated soil - Oluwaseye I Ilesanmi; Abiodun E Adekunle; Japhel A Omolaiye; Efemena M Olorode; Adebayo L Ogunkanmi (Scientific African, 2020)
Lipase enzymes have application in different industrial processes. Screening different habitats for bacteria with lipase activity and optimizing its fermentation parameters will facilitate its effective production and use in industries. In this study, soil sample from a mechanic's workshop in Jericho G.R.A, Ibadan and water sample from Iyake lake, Ado-awaye both in Oyo-state were screened for presence of lipase positive bacterial strains. Culture medium parameters such as carbon source, nitrogen source, pH, inoculum volume and incubation time were varied for the purpose of optimization. Maximum lipase activity was recorded at 12 h incubation. This activity occurred in media with olive oil and yeast which were the best carbon and nitrogen source, respectively. Inoculum volume had an effect of direct proportionality on lipase activity while the isolated organism was determine to be alkalophilic in nature. Under optimized conditions, the organism in the soil sample produced 528.54 U/L lipase activity; showing a 5.3-fold increase in the activity recorded from innate activity. The nucleotide sequence obtained with 16S rRNA gene identified the isolates with highest lipase activity to be Pseudomonas aeuriginosa when subjected to homology search using the Basic Local Alignment Search Tool (BLAST) program. Results obtained showed that lipase obtained from this source could be of potential use in different industrial processes.